Study Of Knowledge Sharing And Intrinsic Motivation On Employee Performance: Study At The Department Of Industry And Trade Pemalang Regency - Sri Wahyuni; Siswanto Siswanto; Ade Novitasari (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to examine and analyze the influence of knowledge sharing and intrinsic motivation on the Pemalang Regency Industry and Trade Service’s non-state civil servant employees.. This research was carried out using a quantitative approach, data was collected through distributing questionnaires and a sample of 79 non-ASN employees at the Pemalang Regency Industry and Trade Department. The sampling technique uses the census method or saturated sample, while data analysis in this research uses path analysis. The results of the analysis show that knowledge sharing has a positive and significant effect on employee performance. Intrinsic motivation has a positive and significant effect on employee performance. Knowledge sharing has a positive and significant effect on job satisfaction. Intrinsic motivation has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. The results of the path analysis test stated that job satisfaction was proven to have a mediating role only in the influence of knowledge sharing on employee performance.